In-situ fabrication of CuS/g-C3N4 nanocomposites with enhanced photocatalytic H2-production activity via photoinduced interfacial charge transfer. (27th April 2017) - Chen, Tianjun; Song, Chengjie; Fan, Mingshan; Hong, Yuanzhi; Hu, Bo; Yu, Longbao; Shi, Weidong
Abstract: In this work, novel CuS/g-C3 N4 composite photocatalysts were successfully prepared via a simple in-situ growth method. CuS nanoparticles, with an average diameter of ca.10 nm, were well dispersed on the surface of g-C3 N4, revealing that g-C3 N4 nanosheets were promising support for in-situ growth of nanosize materials. The CuS/g-C3 N4 composites exhibited highly enhanced visible light photocatalytic H2 evolution from water-splitting compared to pure g-C3 N4 . The optimum photocatalytic activity of 2 wt% CuS/g-C3 N4 composite photocatalytic H2 evolution was about 13.76 times higher than pure g-C3 N4 . The enhanced photocatalytic activity is attributed to the interfacial charge transfer (IFCT). In this system, electrons in the valence band (VB) of g-C3 N4 can transfer directly to CuS clusters, causing the reduction of partial CuS to Cu2 S, which can act as an electron sink and co-catalyst to promote the separation and transfer of photo-generated electrons. The accumulated photoinduced electrons in CuS/Cu2 S clusters could effectively reduce H + to produce H2 . This work provides a possibility for constructing low-cost CuS as a substitute for noble metals in the photocatalytic production of H2 via a facile method based on g-C3 N4 . Highlights: CuS/g-C3 N4 photocatalysts were synthesized by in-situ growth method. The catalysts showed excellent H2 -production activity. The enhanced photocatalytic mechanism was based on interfacial charge transfer.